Pelikula a video documentary on Philippine film (Manila Cultural Center of the Philippines, 1989)
Traces the history of moviemaking in the Philippines, featuring film clips from movies produced from the 1930's to the present, representing the major commercial genres- musical, melodrama, comedy and action movies- as well as the new cinema and the alternative films.
Beta format.
Script, Bienivido L. Lumbera ; direction, Agustin L. Sotto.
Keywords: Motion pictures -- Philippines -- History